Pengaruh Work-Life Balance Dan Lingkungan Kerja Terhadap Kinerja Guru: Survei Pada Guru SMPN 1 Kersamanah - Fadillah Ahmad Rifa’i; Suci Putri Lestari; Gian Riksa Wibawa (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study aims to determine the effect of work-life balance and work environment simultaneously or partially on the performance of SMPN 1 Kesamanah teachers. survey. With a research sample of 60 teachers as respondents to SMPN 1 Kesamanah based on 60 known population data. The data used is primary data. The analytical tool used in this study is multiple linear regression using the SPSS support application version 25. Simultaneously work-life balance and work environment have a significant effect on teacher performance. Partially, the work-life balance variable has a significant effect on teacher performance, as well as the work environment variable, which partially has a significant effect on teacher performance.